Exploring the modulation of the Nav1.7 voltage-gated sodium channel by a centipede venom peptide - Kerry, Amy (2019)
Voltage gated sodium channels are integral transmembrane proteins, their architecture comprises of pore-forming α-subunits associated with one or more auxiliary β-subunits. Nav1.7 is a sodium channel subtype expressed in sensory neurones in the dorsal root ganglia and is known to be involved in nociceptive pain. Thus, there is growing interest in animal toxins that target NaV1.7. Centipedes are among the oldest terrestrial arthropods; minimal clinical significance of stings means they have been overlooked compared to other venomous clades. Encounters with centipedes result in excruciating pain in humans and instant rigid paralysis in prey. Because of the emerging use of animal venoms in novel drug development and as tools to study ion channels, a venom peptide (peptide I) isolated from male Scolopendra hardwickei centipede was utilized to investigate the activity against the Nav1.7 channel. Characterisation of sodium currents expressed by the TE671 cell line using whole-cell patch clamp was initially studied. Sodium currents were completely blocked by tetrodotoxin at a concentration of 1µM and with an IC50 value of 7.4 nM. To assess the effects of peptide I on Nav1.7 we analysed sodium current amplitudes at a threshold potential and the voltage dependence of channel activation. Peptide I induced a concentration-dependent hyperpolarising shift in activation, shifting V50.act from -22.9 ± 3.5 to -33.9 ± 0.8 mV at 10µM. Peptide I isolated from S. hardwickei has Nav1.7 modifying activity resulting in a gain of function of sodium currents. Because of the modulation of the voltage sensitivity of Nav1.7, it could be speculated that peptide I interacts with the voltage-sensing domain, specifically at the previously characterised site 4 where β-scorpion binds. These results report of a hyperpolarising shift in channel activation, a feature undocumented in centipedes. This novel feature provides a starting point for further investigations into other modulating peptides in centipede venom and the location of their binding sites. Unravelling the mechanism behind venom peptides prompts the discovery of novel drugs and pesticides.